Kajian Interpretasi Hadis Tentang Larangan Bagi Anak-anak untuk Keluar Rumah saat Magrib - Abdullah Muhammad Yusron; Muhammad, Muhammad (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
This research discusses the study of the interpretation of the hadith prohibiting children from leaving the house at Maghrib. This research is library research using a normative and methodological approach. The data comes from verses, hadith, and books of the ulama and is then collected and processed using the content analysis method. The results of this research show that if studied textually, the Prophet Muhammad saw. gave orders to parents to restrain their children from leaving the house at Maghrib. Meanwhile, intertextually, this hadith conveys the power of Satan at night, and the dangers that can arise from other creatures roaming around at night. Contextually, it can be understood from this hadith that there are several important things that must be taken into account, namely the responsibility of parents towards their children, the danger of satanic evil at night, and the importance of always fortifying oneself by increasing the remembrance of Allah.